Comparative analysis of the results of the anterior cruciate ligament reconstruction using an autograft preparation by known and new methods - D. B. Balzhinimaev; I. N. Mikhaylov; M. E. Puseva; N. V. Tishkov (Acta Biomedica Scientifica)
Background. To date, the problem of choosing the optimal graft for anterior cruciate ligament (ACL) reconstruction and the methods for its formation is one of the main trends in the surgical treatment of patients with anterior knee joint instability.The aim. To compare the results of the anterior cruciate ligament reconstruction using the known method and the new proposed method for autograft formation.Materials and methods. The results of treatment of ACL injury in 44 patients were assessed. In the main group (19 patients), an original technique of ACL reconstruction from 1/2 of the width of m. peroneus longus tendon was used. In the control group (25 patients), ACL reconstruction was performed using a graft from the m. semitendinosus tendon prepared by the Lubowitz method.Results. The mean difference in the circumference of the distal third of the hip in the main group was 1.57 ± 1.162 cm and was statistically significantly better than in the control group, where the mean difference in the hip circumference was 4.74 ± 1.7207 cm.The range of motion of the knee joint in the main group 3 months after the surgery was 128.42 ± 9.287°, and in the control group mean flection was 109.6 ± 9.120°.The functional results in the main group were assessed by the Lisholm scale and were statistically significantly better than the results in the control group. The functional results by the AOFAS (American Orthopedic Foot & Ankle Society) scale in the main group were 100 points before the surgery and at all terms after the surgery: this indicates that the use of 1/2 of the width of m. peroneus longus tendon does not cause the its functional impairement.Conclusion. Anterior cruciate ligament plasty with use of 1/2 of the width of m. peroneus longus tendon prepared by the proposed method showed statistically significantly better results compared to the preparation of autograft from semitendinous muscle tendon using known method.